Comparison of Results of Fluconazole Disk Diffusion Testing for Candida Species with Results from a Central Reference Laboratory in the ARTEMIS Global Antifungal Surveillance Program - Pfaller, M. A. (American Society for Microbiology, 2004)
The accuracy of antifungal susceptibility tests is important for accurate resistance surveillance and for the clinical management of patients with serious infections. Our main objective was to compare the results of fluconazole disk diffusion testing of Candida spp. performed by ARTEMIS participating centers with disk diffusion and MIC results obtained by the central reference laboratory. A total of 2,949 isolates of Candida spp. were tested by NCCLS disk diffusion and reference broth microdilution methods in the central reference laboratory. These results were compared to the results of disk diffusion testing performed in the 54 participating centers. All tests were performed and interpreted following NCCLS recommendations. Overall categorical agreement between participant disk diffusion test results and reference laboratory MIC results was 87.4%, with 0.2% very major errors (VME) and 3.3% major errors (ME). The categorical agreement between the disk diffusion test results obtained in the reference laboratory with the MIC test results was similar: 92.8%. Likewise, good agreement was observed between participant disk diffusion test results and reference laboratory disk diffusion test results: 90.4%, 0.4% VME, and 3.4% ME. The disk diffusion test was especially reliable in detecting those isolates of Candida spp. that were characterized as resistant by reference MIC testing. External quality assurance data obtained by surveillance programs such as the ARTEMIS Global Antifungal Surveillance Program ensure the generation of useful surveillance data and result in the continued improvement of antifungal susceptibility testing practices.